PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU DI SEKOLAH DASAR NEGERI 5 SINTANG - Simson, Simson; Chiar, Chiar; Fadillah, Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ The principal is a leader in a school institution that has a very important role as managers, leaders, motivators in educational institutions, and responsible in fostering subordinates of teachers, administrative staff to achieve the goal of hope in improving the quality of school. The focus of the problem in this research is: "How is the principal's role in improving the quality of school in SD Negeri 5 Sintang. With the sub-problems: (1) how the principal's role as manager in improving the quality in SD Negeri 5 Sintang, (2) how the principal's role as the leader towards quality improvement in SD Negeri 5 Sintang, (3) the role of principal as motivator in improving quality in SD Negeri 5 sintang, (4) Any obstacles found by the principal in improving the quality in SD Negeri 5 Sintang. The method used in this study is a qualitative research method that is to describe and understand the role of the principal in improving the quality. Subjects in this study are the principal of SD Negeri 5 Sintang, Class Teacher and Head of Administration. The result of this research is that the principal has done his best to carry out his duties as manager, leader, and motivator to provide direction, motivation and encouragement to all school people to perform their duties.Â Keywords : Role of Principal As Manager, Leader, Motivator and School Quality